A abdução em Peirce: um estudo hermenêutico - Souza, Jesaías da Silva [UNESP] (2014)
In this research the goal is to expose the understanding of what is the abduction for Peirce, from a hermeneutic analysis such as it is treated by researchers from UNESP/RC bound to Mathematic Education Post-Graduation Program and to ideas of Hans Georg Gadamer (1999). For that, the question that guided the research is: What is abduction?. The hermeneutic study of Peirce's texts, especially at The Collected Papers of Charles Sanders Peirce compound of eight volumes, is presented in two boards which bring Nuclear Ideas (I.N.) that, by analysis, take us to the categories: feature, procedure and definition. The interpretation of these features allow us to say the abduction, in Peirce, is a logic reasoning, an inferential act which origin at action of question being a type of reasoning that differs from classic logic by the way how it opens possibilities of a new intelligibility of what it's seen, from what it can express when is developed a new explanation of seen. Perceiving the features of abduction it can see how it opens possibilities for a production of the mathematic knowledge giving shape to the concept, that is expressed by a language that expose the direction of produced